PENGOLAHAN AIR PAYAU DENGAN PEMBUBUHAN BESI (II) SULFAT MENGGUNAKAN SARINGAN PASIR SILIKA UNTUK MENGHASILKAN AIR BERSIH - Sarwoko Mangkoediharjo (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2005)
The objective of this research is to assess the limits of chloride concentration in brackish water which can be treated by ferrous sulphate addition to produce clean water. Two types of brackish water were examined, i.e. artificial brackish water and natural brackish water from shallow wells in Sutorejo, Surabaya. The artificial brackish water is made of NaCl solutions which contains 0,6 g Cl-/L, 1,2 g Cl-/L, and 3,65 g Cl-/L. Separation of salt flock from the solution was carried out in silica sand filter. The particle size of silica sand was 2,36 mm and 1,18 mm. Results of the treatments were, brackish water which contains chloride up to 1,2 g Cl-/L were appropriate to be treated by ferrous sulphate to produce chloride less than 0,6 g Cl-/L in accordance with Indonesian clean water quality standard. Addition of ferrous sulphate for the ratio of FeSO4/NaCl = 1,07–2,14 were appropriate to be used without significant influence on process production. The efficiency of chloride deconcentration achieved to about 84%. The particle size of silica sand of 2,36 mm and 1,18 mm did not influence to the quality of treated water for brackish water up to 1,2 g Cl-/L, however, the particle size of 1,18 mm was more efficient for brackish water more than 1,2 g Cl-/L.